# Reduction of the Y combinator

The Y combinator expression is as follows: $$Y \equiv \lambda f .(\lambda x .f(xx) )) .(\lambda x .f(xx) )$$

Now , if I am not wrong , then this expression can be reduced by seeing this as the argument: $.(\lambda x .f(xx))$ hence would lead to the consumption of first bound variable giving: $$(\lambda x .\lambda x .f(xx) (xx))$$

which is equivalent to $\lambda xx .f(xx) (xx)$

which will yield $f(xx)$.

But in my book I don't find the Y combinator being reduced to this and it made me feel that something is fishy with the reduction that I am doing .

Is there any mistake in this?

You've misread the definition of $Y$. $(\lambda x.f(xx))) (\lambda x.f(xx))$ is the body of the function. You can put an additional pair of parentheses in the definition: $$Y = \lambda f. \color{red}{\mathbf{(}} (\lambda x.f(xx))) (\lambda x.f(xx)) \color{red}{\mathbf{)}}$$ Beware that different authors use different conventions for parentheses. But under the most common convention, $\lambda$ has lower precedence than application, so the body of a lambda goes until the next enclosing closing parenthesis. If a text uses a different convention, make sure to put parentheses accordingly.
You can reduce $Y$, but the argument $(\lambda x.f(xx)))$ is applied to $(\lambda x.f(xx))$. The $\lambda f. \ldots$ doesn't change since it isn't applied to anything. \begin{align} Y \;\; = \; & \lambda f. (\lambda \color{magenta}{x}.f(\color{magenta}{x}\color{magenta}{x}))) \color{magenta}{(\lambda x.f(xx)))} \\ \rightarrow_\beta \; & \lambda f. f \left( (\lambda x.f(xx))) (\lambda x.f(xx))) \right) \\ \end{align} Let $\Omega_f = (\lambda x.f(xx)) (\lambda x.f(xx))$, so that $Y = \lambda f. \Omega_f$. The reduction above is $\lambda f. \Omega_f \rightarrow_\beta \lambda f. f \Omega_f$. That's $\Omega_f \rightarrow_\beta f \Omega_f$ under the context $\lambda f. []$. There's an infinite chain of reductions $$Y = \lambda f. \Omega_f \rightarrow_\beta \lambda f. f \Omega_f \rightarrow_\beta \lambda f. f (f \Omega_f) \rightarrow_\beta \lambda f. f (f (f \Omega_f)) \rightarrow_\beta \ldots$$ This is how the recursion combinator works. But this won't do anything “useful” until $f$ is replaced by a lambda so that the $f \Omega_f$ part can be reduced.
If you apply $Y$ to a function $g$, a redex appears at the top level. \begin{align} Y g \;\; = \;\; & \left( \color{green}{\lambda f}. (\lambda x.\color{green}{f}(xx))) (\lambda x.\color{green}{f}(xx)) \right) \color{green}{g} \\ \rightarrow_\beta \; & (\color{darkblue}{\lambda x}. g(\color{darkblue}{x} \color{darkblue}{x})) \color{darkblue}{(\lambda x. g(x x))} \\ \rightarrow_\beta \; & g \left( (\lambda x. g(x x)) (\lambda x. g(x x)) \right) \\ \leftarrow_\beta \; & g \left( \left( \color{brown}{\lambda f}. (\lambda x. \color{brown}{f}(x x)) (\lambda x. \color{brown}{f}(x x)) \right) \color{brown}{g} \right) \\ = \; & g (Y g) \end{align}
• Actually, there is a way to reduce $Y$, since $\to_\beta$ reduces under lambdas. In certain reduction strategies, this is disallowed, but reducing under lambdas is allowed in the standard theory (e.g. Barendregt's). So, writing $Z$ for $\lambda x.f(xx)$, we have $Y=\lambda f.ZZ \to_\beta \lambda f.f(ZZ) \to_\beta f(f(ZZ)) \to_\beta \ldots$ without ever reaching normal form. Of course, the result of this reduction is not that useful, albeit one can see it as a hint about a fixed point being computed. Passing an additional argument $g$ as you did makes it much clearer, though.